Novel therapeutic strategies targeting tumor-stromal interactions in pancreatic cancer - Hamada, Shin; Masamune, Atsushi; Shimosegawa, Tooru (Frontiers in Physiology, 2013)
Therapy-resistance and postoperative recurrence are causes of the poor prognosis in pancreatic cancer. Conventional therapies have a limited impact on the control of pancreatic cancer, resulting in the rapid re-growth of the tumor. The indispensable role of tumor-stromal interaction, which acts as a defender of cancer cells and enhances malignant potential, is being uncovered now. For example, specific signaling pathways for desmoplasia induction have been identified, such as sonic hedgehog or connective tissue growth factor, whose inhibition causes desmoplasia depletion and therapeutic advantages. Revolutions in drug delivery methods have led to the establishment of novel chemotherapeutic regimens, with better patient survival. Furthermore, mechanisms of immunosuppression in the pancreatic cancer-bearing host were clarified by the identification of myeloid-derived suppressor cells, which also promote disease progression. Strategies to target these components of the tumor stroma revealed certain anticancer effects in vitro and in vivo, suggesting the possibility of stroma-targeting therapy. Suppression of the stromal cell function increases the sensitivity of pancreatic cancer cells to therapeutic intervention. Further study will clarify the complex nature of the tumor microenvironment, the targeting of which should lead to better clinical outcomes.